Revising degumming and bleaching processes of palm oil refining for the mitigation of 3-monochloropropane-1,2-diol esters (3-MCPDE) and glycidyl esters (GE) contents in refined palm oil - Hew, Khai Shin; Asis, Ahmad Jaril; Tan, Tai Boon; Mat Yusoff, Masni; Lai, Oi Ming; Nehdi, Imeddedine Arbi; Tan, Chin Ping (Elsevier Ltd, 2020)
Corresponding the high presence of 3-monochloropropane-1,2-diol esters (3-MCPDE) and glycidyl esters (GE) in refined palm oil, this paper re-evaluated degumming and bleaching processes of physical palm oil refining to reduce the amount of said contaminants. Separation-free water degumming was incorporated into the process, and this significantly (p < 0.05) reduced the esters content without compromising other oil qualities. Different types of bleaching earth (BE) were dosed at 0.5, 1.0 and 1.5% to investigate their effects on the esters formation. Results showed that different type of BE had their own optimal dosage for minimum esters formation. Surface acidity was confirmed as the key performance determinant of BE in mitigation of 3-MCPDE and GE in oil rather than the porosity profile. Specifically, BE with high acidity should be avoided, but slightly acidic BE (pH ≃ 5) was found to provide the greatest reduction of esters as compared to natural and neutral activated BE.